Immunometabolism in haematopoietic stem cell transplantation and adoptive cellular therapies. Issue 6 (November 2020) - Braverman, Erica L.; Waltz, Gail; Byersdorfer, Craig A.
Abstract : Purpose of review: Controlling T cell activity through metabolic manipulation has become a prominent feature in immunology and practitioners of both adoptive cellular therapy (ACT) and haematopoietic stem cell transplantation (HSCT) have utilized metabolic interventions to control T cell function. This review will survey recent metabolic research efforts in HSCT and ACT to paint a broad picture of immunometabolism and highlight advances in each area. Recent findings: In HSCT, recent publications have focused on modifying reactive oxygen species, sirtuin signalling or the NAD salvage pathway within alloreactive T cells and regulatory T cells. In ACT, metabolic interventions that bolster memory T cell development, increase mitochondrial density and function, or block regulatory signals in the tumour microenvironment (TME) have recently been published. Summary: Metabolic interventions control immune responses. In ACT, efforts seek to improve the in-vivo metabolic fitness of T cells, while in HSCT energies have focused on blocking alloreactive T cell expansion or promoting regulatory T cells. Methods to identify new, metabolically targetable pathways, as well as the ability of metabolic biomarkers to predict disease onset and therapeutic response, will continue to advance the field towards clinically applicable interventions.